Numerical Analysis for an Electro‐Magneto‐Mechanical Phenomenon with High‐Order Accurate Methods. Issue 1 (25th January 2021) - Gleim, Tobias; Chen, Hefeng
Abstract: This paper establishes an axisymmetric model for a levitation device. Therein, the Maxwell equations are combined with the balance of linear momentum. Different possible formulations to describe the MAXWELL equations are presented and compared and discussed in the example. A high order finite element discretization using GALERKIN's method in space and the generalized NEWMARK‐α method in time are developed for the electro‐magneto‐mechanical approach. Several studies on spatial and temporal discretization with respect to convergence will be investigated. In addition, the boundary influences and the domain size with respect to the levitation device are also examined.